Teaching Across Borders: Reflective Practice and Professional Learning in Transnational Educational Contexts - Rustamova, Dzhonbibi (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
This article examines professional learning through reflective practice in transnational teaching contexts. Drawing on qualitative practitioner inquiry informed by teaching experience in Tajikistan, Russia, the United Kingdom, and online instruction for learners in Afghanistan, the study explores how teachers develop adaptive expertise through cross-contextual pedagogical work. Using reflective journals, teaching artefacts, and comparative analysis, the article identifies key dimensions of professional development emerging from transnational practice, including pedagogical adaptation, ethical judgment, and evolving teacher identity. The findings suggest that reflective engagement with culturally and politically diverse contexts functions as a powerful form of professional learning, often exceeding the impact of formal professional development programmes. The article contributes to international scholarship on teacher professional development by conceptualising transnational teaching as a site of situated, reflective expertise with implications for teacher education and global education initiatives.